2022
DOI: 10.13040/ijpsr.0975-8232.13(10).39231
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The present study aimed to study the effect of the drug Xymedon and its conjugate with L-ascorbic acid exhibiting hepatoprotective activity on the apoptosis of rat liver cells against the background of the influence of hepatotoxic agent tetrachloromethane. Though the general effects of Xymedon and its conjugates with various biogenic acids have been studied, the molecular markers affected by the compounds have not yet been established. Experimental methods of investigation included modeling of toxic liver dama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
1
0
0
Order By: Relevance
“…Conversely, the treatment of compound 2 not only restored liver tissue structure but also signi cantly increased collagen ber remodeling, decreased liver mass coe cient, and showed the trend of reduced COX-2 expression compared to the CCl 4 + ethanol control group. Thus, this study, as well as our previous work, demonstrated the higher e cacy of the compound 2 compared to the compound 1 in the treatment of both acute toxic liver injury [35] and chronic liver injury models [16].…”
Section: Discussionsupporting
confidence: 64%
“…Conversely, the treatment of compound 2 not only restored liver tissue structure but also signi cantly increased collagen ber remodeling, decreased liver mass coe cient, and showed the trend of reduced COX-2 expression compared to the CCl 4 + ethanol control group. Thus, this study, as well as our previous work, demonstrated the higher e cacy of the compound 2 compared to the compound 1 in the treatment of both acute toxic liver injury [35] and chronic liver injury models [16].…”
Section: Discussionsupporting
confidence: 64%